Non-canonical CRL4A/4B(CDT2) interacts with RAD18 to modulate post replication repair and cell survival. - Sarah Sertic; Claudio Evolvi; Emanuela Tumini; Paolo Plevani; Marco Muzi-Falconi; Giuseppe Rotondo (PLoS ONE)
The Cullin-4(CDT2) E3 ubiquitin ligase plays an essential role in DNA replication origin licensing directing degradation of several licensing factors at the G1/S transition in order to prevent DNA re-replication. Recently a RAD18-independent role of Cullin-4(CDT2) in PCNA monoubiquitylation has been proposed. In an effort to better understand the function of Cullin-4(CDT2) E3 ubiquitin ligase in mammalian Post-Replication Repair during an unperturbed S-phase, we show that down-regulation of Cullin-4(CDT2) leads to two distinguishable independent phenotypes in human cells that unveil at least two independent roles of Cullin-4(CDT2) in S-phase. Apart from the re-replication preventing activity, we identified a non-canonical Cullin-4(CDT2) complex, containing both CUL4A and CUL4B, associated to the COP9 signalosome, that controls a RAD18-dependent damage avoidance pathway essential during an unperturbed S-phase. Indeed, we show that the non-canonical Cullin-4A/4B(CDT2) complex binds to RAD18 and it is required to modulate RAD18 protein levels onto chromatin and the consequent dynamics of PCNA monoubiquitylation during a normal S-phase. This function prevents replication stress, ATR hyper-signaling and, ultimately, apoptosis. A very similar PRR regulatory mechanism has been recently described for Spartan. Our findings uncover a finely regulated process in mammalian cells involving Post-Replication Repair factors, COP9 signalosome and a non-canonical Cullin4-based E3 ligase which is essential to tolerate spontaneous damage and for cell survival during physiological DNA replication.